Keberadaan Awig-Awig dalam Mengatasi Aksi Tindak Pidana Ringan di Desa Marga Kabupaten Tabanan, Bali - I Nengah Wijana; Deli Bunga Saravistha (Indra Institute Research & Publication, 2023)
The existence of customary law itself is recognized in Indonesian positive law, namely in the 1945 Constitution of the Republic of Indonesia Article 18 B paragraph (2). Customary law has its own uniqueness according to the custom in which the law lives, so it is not uncommon for there to be differences between customary law in one area and another. Several regions in Indonesia that have strong cultural characteristics still practice customary laws that have been enforced for a long time, such as Aceh which still uses Islamic law and Bali which also uses customary law guidelines to resolve problems that arise in society known as Awig-Awig. Awig-awig comes from the word